Law and society : an introduction - Watts, John Harrison (CRC Press, 2014)
"In recent years, legal studies have increased the focus on contemporary social issues involved in law and society. This volume discusses the traditional subjects covered in other law and society texts and eliminates the need for a separate reader by also including chapters on controversial legal topics including affirmative action, education, the death penalty, right to work laws, and abortion. Each chapter builds on the previous ones and includes concrete examples of the issues involved. Supplemented with ample pedagogical features, the book is designed to encourage students in the development of new insights on the relationships between law and society. "